2020
DOI: 10.1002/adma.202001943
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Voltage Manipulation of Ferromagnetism

Abstract: Spintronic elements based on spin transfer torque have emerged with potential for on-chip memory, but they suffer from large energy dissipation due to the large current densities required. In contrast, an electric-fielddriven magneto-electric storage element can operate with capacitive displacement charge and potentially reach 1-10 J cm 2 switching operation. Here, magnetoelectric switching of a magnetoresistive element is shown, operating at or below 200 mV, with a pathway to get down to 100 mV. A combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 28 publications
(30 reference statements)
1
34
0
Order By: Relevance
“…As observed, the LBFO consistently switches faster than its BFO counterpart. Within the BFO system, it has been shown experimentally that lanthanum substitution reduces the rhombohedral distortion thereby lowering the magnitude of the remnant polarization and the coercive field [25,26]. Similarly, density-functional-theory calculations show that lanthanum substitution reduces both the potential-energy barrier between, and magnitude of, the degenerate ground states of polarization [25,26].…”
mentioning
confidence: 96%
“…As observed, the LBFO consistently switches faster than its BFO counterpart. Within the BFO system, it has been shown experimentally that lanthanum substitution reduces the rhombohedral distortion thereby lowering the magnitude of the remnant polarization and the coercive field [25,26]. Similarly, density-functional-theory calculations show that lanthanum substitution reduces both the potential-energy barrier between, and magnitude of, the degenerate ground states of polarization [25,26].…”
mentioning
confidence: 96%
“…High density, high‐speed, and low power consuming nonvolatile memories are currently being vigorously explored for use in next‐generation computation, particularly due to the performance gap between the logic and memory elements of the current computational architecture. [ 1–3 ] Of various explored material systems, electrically switchable spontaneous polarization of ferroelectric materials enables a robust nonvolatile memory solution. [ 4–6 ] One such promising memory element is the ferroelectric tunnel junction (FTJ), which, unlike ferroelectric RAM, offers nondestructive readout, in addition to low operation energy and high operation speed.…”
Section: Figurementioning
confidence: 99%
“…Efforts in this direction are currently being undertaken. For example, magnetoelectric switching of a magnetoresistive element was recently shown to operate at or below 500 mV, with a pathway to get down to 100 mV [136]. A combination of phase detuning is utilized via isovalent lanthanum substitution and thickness scaling in BiFeO 3 to scale the switching energy density to ≈ 10 µJ cm −2 .…”
Section: Electric-field Control Of Magnetic Statementioning
confidence: 99%
“…They key to this work was leveraging effects of lanthanum substitution which is known to both lower the polarization and the ordering temperature (and therefore the energy of switching) of the ferroelectric and to take advantage of innate thickness scaling effects (thinner films require smaller voltages for switching). In turn, the researchers showed that the switching voltage of the giant magnetoresistance (GMR) response can be progressively reduced from ≈ 1 V to ; c is the corresponding piezoelectric phase data showing switching of the polar state at~500 mV for the 20 nm LBFO layer; also shown are the corresponding XMCD-PEEM (at the Co-edge) for a CoFe dot that has been switched (from BLACK to WHITE) with a bias of 500 mV; d is the corresponding XMCD-PEEM data for a CoFe dot on a 10 nm LBFO layer showing switching at~200 mV [136] 500 mV by a reduction of the film thickness down to 20 nm (Fig. 21a).…”
Section: Electric-field Control Of Magnetic Statementioning
confidence: 99%